The distribution study of red Meranti group (shorea ovalis, shorea macroptera,shorea acuminata) in UiTM Jengka forest reserve (base line 1 : line 11 - 20) / Mohamad Saiful Sulaiman, Muhamad Nasrulrahman Che Kar and Mohd Adli Hamzah - Sulaiman, Mohamad Saiful; Che Kar, Muhamad Nasrulrahman; Hamzah, Mohd Adli (2011)
The study was conducted in UiTM Jengka Forest Reserve on the base line: lines 11 - 20. The main purpose of this study was to determine the distributions of goods from a group of Red Meranti are Meranti Kepong (Shorea Ovalis), Meranti Melantai (Shorea Macroptera) and Meranti Rambai Daun (Shorea Acuminata). The method is carried out to study the inventory method in which the forest path at depth 20 meters (10 feet right and left) and the forest is 575 meters long (lines 11-20). This means that forests are studied from the line 11-20 is 20 m X 575 m. The entire forest area of the strip 11 to 20 is 230,000 m2 , or 42.2% of the total area of forest. From the study, we found that 46 were Meranti Kepong, 41 were Meranti Melantai and 13 are Meranti Meranti Rambai leaves. Meranti Kepong is a lot of trees found in UiTM Jengka forests as areas of learning because It favors low lying land and stream valley, in which latter habitat it may be found at altitude over 500 m. From observations of this study, it covers 46% of the total 10 lines in the forest Jengka UiTM.